Interdisciplinarity of Cultural Heritage Conservation Making and Makers: Through Diversity Towards Compatibility of Approaches - Lobovikov-Katz, Anna; Martins, João; Ioannides, Marinos; Sojref, Dalik; Degrigny, Christian (My University, 2018)
In conservation of cultural heritage (CCH), experts from diverse areas of knowledge work together, each of them contributing unique expertise. However, in modern dynamic multi- and interdisciplinary collaboration, new contributors often remain conservation outsiders, being deeply submerged in their own research areas with regard to their research methods, their view of hierarchy of aims and values of conservation of cultural heritage, etc. Their understanding of targets of input and outcome of their compartmentalized contribution to specific conservation problems might be incompatible with the principles and criteria of modern CCH, thus affecting productivity of such contribution. This paper focuses on this conflict by examining selected relevant aspects based on the experience of the collaborative interdisciplinary research in conservation of cultural heritage.
Keywords: Compatibility; Conservation of cultural heritage (CCH); Interdisciplinarity; Interdisciplinary research